La Recaudación Del Impuesto Predial En El Municipio De Chihuahua: Un Análisis De Las Causas Del Rezago - Ramos, Pedro Javier Martínez; Baeza, Martín Venegas; Cisneros, Hilda Cecilia Escobedo; Bencomo, Myrna Isela García (European Scientific Journal, ESJ, 2018)
In order to determine the main reasons for the lag in the payment of the Property Tax of the Municipality of Chihuahua and to ascertain if there is a culture of nonpayment in the taxpayers, an investigation was carried out in this regard. The hypothesis proposed was that the main reason for the lag in the payment of the property tax was the lack of economic resources. The nature of the research was quantitative, descriptive, non-experimental, and transectional. The macro variable to be analyzed was lagged in the payment of taxes. The sampling frame was confirmed by the list of taxpayer debtors of the property tax. A confidence level of 95% and margin of error of 5% was used in the study. This, however, was drawn from a sample of 375 contributors to whom the survey designed by the researchers was applied. These were applied randomly in a shopping center in the city. The stated objectives were met and it was found that 6% of respondents have a culture of non-payment, while 94% plan to pay. The major reason the taxpayer debtors could not pay the tax was attributed to the lack of economic resources. As a result, the hypothesis was not rejected.